KLRG1 negatively regulates natural killer cell functions through the Akt pathway in individuals with chronic hepatitis C virus infection - Wang, Jia M; Cheng, Yong Q; Shi, Lei; Ying, Ruo S; Wu, Xiao Y; Li, Guang Y; Moorman, Jonathan P; Yao, Zhi Q (Journal of virology, 2013)
In this study, we demonstrate that killer cell lectin-like receptor subfamily G member 1 (KLRG1), a transmembrane protein preferentially expressed on T cells, is highly expressed on CD56(+) NK cells, which are significantly reduced in their numbers and functions in the peripheral blood of patients with chronic hepatitis C virus (HCV) infection compared to subjects without infection. KLRG1 expression is also upregulated on healthy NK cells exposed to Huh-7 hepatocytes infected with HCV in vitro. Importantly, the expression levels of KLRG1 are inversely associated with the capacity of NK cells to proliferate and to produce gamma interferon (IFN-γ) but positively associated with apoptosis of NK cells in response to inflammatory cytokine stimulation. KLRG1(+) NK cells, including CD56(bright) and CD56(dim) subsets, exhibit impaired cell activation and IFN-γ production but increased apoptosis compared to KLRG1(-) NK cells, particularly in HCV-infected individuals. Importantly, blockade of KLRG1 signaling significantly recovered the impaired IFN-γ production by NK cells from HCV-infected subjects. Blockade of KLRG1 also enhanced the impaired phosphorylation of Akt (Ser473) in NK cells from HCV-infected subjects. Taken together, these results indicate that KLRG1 negatively regulates NK cell numbers and functions via the Akt pathway, thus providing a novel marker and therapeutic target for HCV infection.